An Enhanced Partial Transmit Sequence Based on Combining Hadamard Matrix and Partitioning Schemes in OFDM Systems - jawhar, yasir amer; Ramli, Khairun; Taher, Montadar; Audah, Lukman; Shah, Nor Shahida; Ahmed, Mustafa; Hammoodi, Ahmed (International Journal of Integrated Engineering, 2018)
The partial transmit sequence (PTS) considered as one of the efficient approaches to restrain the high peak to average-power ratio (PAPR) in orthogonal frequency division multiplexing (OFDM) frameworks. PTS relied on partitioning the input data block and rotate them with a set of the phase vectors. In this study, a novel technique is suggested to improve the PAPR reduction performance in the PTS technique by combining Hadamard matrix and the popular kinds of the partitioning schemes interleaving scheme (IL-PTS), adjacent scheme (Ad-PTS), and pseudo-random scheme (PR-PTS). The new approach employed Hadamard matrix to change some of the subcarrier phases of the partitioning scheme in the frequency-domain. The simulation results demonstrated that the new method improved the PAPR diminishment performance better than that of the PR-PTS and Ad-PTS. However, the proposed method achieved the same PAPR performance compared with the IL-PTS scheme.